Synchronous online learning: why some students don’t actively participate - Donelan, Helen; Kear, Karen; Rosewell, Jon; Okada, Ale; Sheehy, Kieron; Amor, Kevin; Edwards, Carol; Mooney, Allan; Cuffe, Paige; Elder, Tracey (Online Learning, 2025)
In the context of online and distance learning, active student engagement in online synchronous tutorials is important for students’ development; yet it can be challenging to achieve. The research reported in this paper explored why some students do not participate actively in online synchronous tutorials, instead preferring passive participation. The research, carried out at a large distance-learning university, employed two large-scale online surveys, one with students and one with tutors, to investigate these issues; over 600 students and almost 200 tutors on a range of modules responded to the surveys. The surveys gathered quantitative and rich qualitative data that provides insights into students’ and tutors’ experiences. The survey data showed that lack of confidence is an important factor affecting student participation; over a third of students indicated that they experience stress when expected to take part actively. The paper also discusses: how the online tools used in synchronous tutorials (e.g. text chat, polls, shared whiteboards) can support different levels of participation; the approaches tutors can use to encourage active engagement; and the role of passive participation.